(untitled) (Research, Society and Development, 2021)
COVID-19 is a respiratory infection caused by Coronavirus, Severe Acute Respiratory Syndrome 2 (SARS-CoV-2). The disease is transmitted through respiratory droplets, coughing, sneezing, shaking hands, objects and surfaces. Objective: to identify the safety measures adopted in the hospital environment to deal with COVID-19. Method: This is an integrative review with a qualitative approach, a method that allows incorporating research, using articles from the years 2019 to 2021, in the VHL libraries and LILACS, MEDLINE, SCIELO databases, using the descriptors (COVID-19), (Hospitals), (Security measures). Results and discussions: In the analyzed articles, it was observed that hospitals were readapted to be able to face the new pandemic, obtaining prevention measures such as the reorganization of care, expansion of intensive care unit beds, increased supply of personal protective equipment, such as masks and protective gowns and acquisition of sufficient test for diagnosis, also creating protocols and strategies regarding the use of PPE and hand hygiene. Final considerations: they report that measures adopted in hospital environments were changes in care, expansion of intensive therapy beds, increase in personal protective equipment (PPE) and acquisition of more tests for diagnosis.